Audit Quality as a Moderator of Auditor Switching Determinants: Evidence from SRI-KEHATI Index Companies in Indonesia - Novia Indah Oktaviani Syahari; Harry Budiantoro (Research of Accounting and Governance, 2026)
This study examines the determinants of auditor switching by analyzing the effects of Audit Committee Gender, Audit Fee, Financial Distress, and Audit Report Lag, with Audit Quality as a moderating variable. Prior studies have primarily focused on general listed companies and have provided limited evidence on the moderating role of audit quality, particularly in sustainability-oriented firms. This study addresses this gap by examining companies included in the SRI-KEHATI Index, which represents firms committed to strong corporate governance, environmental responsibility, and sustainable business practices. Secondary data were collected from audited annual reports of SRI-KEHATI Index companies listed on the Indonesia Stock Exchange during 2019–2023. Using purposive sampling, the study obtained 75 firm-year observations from 16 companies. Logistic regression and Moderated Regression Analysis (MRA) were employed using SPSS. The findings reveal that Audit Committee Gender, Audit Fee, Financial Distress, and Audit Report Lag do not significantly influence auditor switching. In addition, Audit Quality does not moderate the relationships between these variables and auditor switching. These findings suggest that auditor switching decisions in sustainability-oriented firms are influenced by factors beyond financial, operational, and governance characteristics, emphasizing the importance of maintaining auditor independence and consistent audit quality.